PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL, PARTISIPASI ORANG TUA, DAN MOTIVASI BELAJAR DI MASA PANDEMI COVID-19 TERHADAP PRESTASI BELAJAR - Muhammad Fajar Kurniawan; Sutiah Sutiah; Endah K Purwaningtyas (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
The way of learning that is carried out in the education system in Indonesia is to use the classical system or be done face-to-face directly. Conditions in the current state of the COVID-19 pandemic emergency, everyone must do online learning, including in elementary schools. In online learning, students can become less dynamic in conveying goals and thoughts, which can lead to tiring learning. A student who experiences boredom in learning will get progress in learning outcomes. So that teachers use alternatives to support the learning process by using audio-visual media, parental participation and learning motivation. The objectives to be achieved are: To determine the effect of using audio-visual media, parental participation, and learning motivation during the covid-19 pandemic on achievement studying in school. This research method uses a quantitative approach used in this study, namely the quantitative correlational approach. To collect samples using the Problem Examination procedure with a kind of regular randomized examination strategy (Methodical Irregular Examining), with a population of 160, a sample of 32 was obtained. mean scores 3.94, 3.91, and 3.94. 2. Parental participation directly affects the learning achievement of school students in Singkut sub-district with a score of 6.013> 2.048. This means that there is a significant effect between the variables of Parental Participation on learning achievement. 3. The variables using Audio Visual Media, Parental Participation, and Learning Motivation have a value of 57.8% affecting learning achievement obtained from the value of the effective contribution of each variable used in the study, the other 42.2% is influenced by other variables that are not used in research..